Respuesta :

Step-by-step explanation:

4/5x-3=3/10x+7

We move all terms to the left:

4/5x-3-(3/10x+7)=0

Domain of the equation: 5x!=0

x!=0/5

x!=0

x∈R

Domain of the equation: 10x+7)!=0

x∈R

We get rid of parentheses

4/5x-3/10x-7-3=0

We calculate fractions

40x/50x^2+(-15x)/50x^2-7-3=0

We add all the numbers together, and all the variables

40x/50x^2+(-15x)/50x^2-10=0

We multiply all the terms by the denominator

40x+(-15x)-10*50x^2=0

Wy multiply elements

-500x^2+40x+(-15x)=0

We get rid of parentheses

-500x^2+40x-15x=0

We add all the numbers together, and all the variables

-500x^2+25x=0

a = -500; b = 25; c = 0;

Δ = b2-4ac

Δ = 252-4·(-500)·0

Δ = 625

The delta value is higher than zero, so the equation has two solutions

We use following formulas to calculate our solutions:

x1=−b−Δ√2ax2=−b+Δ√2a

Δ−−√=625−−−√=25

x1=−b−Δ√2a=−(25)−252∗−500=−50−1000=1/20

x2=−b+Δ√2a=−(25)+252∗−500=0−1000=0